Lifelong Learning at Universities: Future Perspectives for Teaching and Learning - Eva Cendon (Springer, 2018)
This paper examines practices of teaching and learning in the era of digitalization. More specifically, it addresses practices of teaching and learning for students with professional experience who work alongside their studies. Based on the assumption that digitalization is a means of allowing more open and flexible pathways for teaching and learning in higher education, the paper focusses on the perspectives and perceptions of both students and teachers in digital supported teaching and learning environments as forms of blended learning. It brings together findings from two qualitative empirical studies: one focused on students' perspectives of their development over the course of their studies; the second addressed teachers' perspectives and their teaching strategies and activities. Based on the findings of these two research studies, the paper outlines future perspectives for teaching and learning and the role of digitalization, with a particular emphasis on programs of lifelong learning at universities.